(untitled) (El-Wahat Journal for Research and Studies, 2021)
Globalization Has Become The Term Of The Current Time. It Was A Subject Matter Of Research And Study In The Universities And The Media In Addition To The Different Intellectual, Philosophical And Political Streams And Even Nature And Environmental Scientists. Its Concept Is Widely Related To The Development And Economic Openness, However, It’s Not Like That In Reality, As It Includes All Aspects Of Economic, Political, Cultural, Social And Environmental Life, And About This Topic, Our Essay Will Attempt To Explain The Fundamental Concepts Of Globalization And Its Foundation And Development Arriving At Determining Its Positive And Negative Effects. Keyword- Globalization, Selected Reality And Imposed Reality